Induced EEG activity during the IAPS tests and avEMT in intimate partner violence against women - López López, Juan Manuel; Cárdenas Poveda, D. Carolina; Acero Triviño, María Paula; González Álvarez, Alexandra; Rizo Arévalo, Alejandra; Prado Rivera, Mayerli Andrea; Mejía Soto, Eliana; Velázquez Pérez, Jose Luis; Espitia, Catalina (SPIE, 2018)
Intimate Partner Violence (IPV) against women is a major problem in Colombia. Nowadays the question about the effects of violence on women and the identification of latent risks that affect their health, is increasingly relevant. This article describes a pilot study that aimed to measure electrophysiological signals corresponding to the emotional neurophysiological response of women who had experienced IPV in contrast to those who did not. Six healthy female adults, ranged in age from 18 to 55 years old enrolled in this study. For the measurement we used the International Affective Picture System (IAPS) and an Auditory and Visual Emotional Memory Test (avEMT), and we recorded the EEG signal with a g.Nautilus 32 g.LadyBird. EEG signals acquired from baseline and during the tests were compared. As a result of IAPS test, we found for all the participants a higher power spectrum at low EEG frequencies and a decrease in power as the frequencies increase for baseline and emotional pictures. For the avMET, both groups show a higher power spectrum in the different phases of the task compared with the baseline, with an exception of one participant from the WIPV group who show the opposite tendency. Also, two machine learning models were trained and an accuracy of more than 85% were achieved to classify EEG signals from women who experienced IPV and women who had not. This research is an approach to the phenomenon of violence against women and broadens the understanding of the effects on emotional response and electrophysiological activation in women who have experienced this type of situation.

La violencia de pareja (VPI) contra las mujeres es un problema importante en Colombia. Hoy en día la pregunta sobre los efectos de la violencia en las mujeres y la identificación de los riesgos latentes que afectan su salud, es cada vez más relevante. Este artículo describe un estudio piloto que tuvo como objetivo medir las señales electrofisiológicas correspondientes a la respuesta neurofisiológica emocional de las mujeres que habían experimentado la VPI en contraste con las que no lo hicieron. Seis mujeres adultas sanas, con edades comprendidas entre los 18 y los 55 años, se inscribieron en este estudio. Para la medición se utilizó el Sistema Internacional de Imágenes Afectivas (IAPS) y un Test de Memoria Emocional Auditiva y Visual (avEMT), y se registró la señal EEG con un g.Nautilus 32 g.LadyBird. Se compararon las señales de EEG adquiridas en la línea de base y durante las pruebas. Como resultado de la prueba IAPS, encontramos para todos los participantes un espectro de potencia más alto en las frecuencias bajas del EEG y una disminución de la potencia a medida que aumentan las frecuencias para la línea de base y las imágenes emocionales. Para el avMET, ambos grupos muestran un espectro de potencia más alto en las diferentes fases de la tarea en comparación con la línea de base, con la excepción de un participante del grupo WIPV que muestra la tendencia opuesta. Además, se entrenaron dos modelos de aprendizaje automático y se logró una precisión de más del 85% para clasificar las señales de EEG de las mujeres que habían experimentado la VPI y las que no. Esta investigación supone una aproximación al fenómeno de la violencia contra las mujeres y amplía la comprensión de los efectos sobre la respuesta emocional y la activación electrofisiológica en mujeres que han vivido este tipo de situaciones.
Keywords: Cerebro; Aprendizaje automático (Inteligencia artificial); Visualización; Electroencefalografía; Electroencephalography; Electroencefalografía; Brain; Cerebro; Image segmentation; Segmentación de imágenes; Visualization; Visualización; Machine learning; Aprendizaje automático; MATLAB; MATLAB; Brain mapping; Mapeo del cerebro